2008
DOI: 10.1016/j.neubiorev.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 nicotinic acetylcholine receptor: A link between inflammation and neurodegeneration

Abstract: Alzheimer's disease (AD) is the leading cause of dementia affecting over 25 million people worldwide. Classical studies focused on the description and characterization of the pathological hallmarks found in AD patients including the neurofibrillary tangles and the amyloid plaques. Current strategies focus on the etiology of these hallmarks and the different mechanisms contributing to neurodegeneration. Among them, recent studies reveal the close interplay between the immunological and the neurodegenerative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 149 publications
2
59
0
1
Order By: Relevance
“…[43][44][45][46] Therefore, we investigated the role of the ␣7nAChR in inflammation and EOD in renovascular hypertension using ␣7nAChR Ϫ/Ϫ mice. After induction of 2K1C hypertension, ␣7nAChR Ϫ/Ϫ mice displayed greater serum levels of proinflammatory cytokines (⌱L-1␤ , IL-6, and TNF-␣) and more severe EOD than WT mice.…”
Section: Et Al ␣7nachr and Hypertensive Organ Damage 303mentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46] Therefore, we investigated the role of the ␣7nAChR in inflammation and EOD in renovascular hypertension using ␣7nAChR Ϫ/Ϫ mice. After induction of 2K1C hypertension, ␣7nAChR Ϫ/Ϫ mice displayed greater serum levels of proinflammatory cytokines (⌱L-1␤ , IL-6, and TNF-␣) and more severe EOD than WT mice.…”
Section: Et Al ␣7nachr and Hypertensive Organ Damage 303mentioning
confidence: 99%
“…12 At the same time, the aorta was cleaned of adhering fat and connective tissue. A leupeptin (50 µg/ml), aprotinin (25 µg/ml), pesptatin A (10μg/ml) and dithiothreitol 43 (DTT2 mmol/L). The supernatant was obtained by centrifugation at 11,000 g for 15 min 44 at 4°C.…”
mentioning
confidence: 99%
“…Recent work has shown that ACh released from cholinergic axon terminals can interact with α7 nicotinic ACh receptors (nAChRs) on vicinal immune cells [38,39] . The nicotinic receptors then translate the cholinergic signal into suppression of cytokine release [37,40] .…”
Section: Cholinergic Deficiency In Vad Animal Models and Vad Patientsmentioning
confidence: 99%
“…Also, functional nACh receptors in some amygdala nuclei (like the basolateral complex) are predominantly 7-containing receptors [22]. These receptors are believed to play an antiinflammatory and neuroprotective role in neurodegenerative diseases and in stressful situations [23][24][25]. Concerning these observations, the aim of this work was to determine the density of 7 nicotinic receptors in the hippocampus, cortex and amygdala of rats submit-ted to the infusion of A peptide and correlate this with sustained attention.…”
Section: Introductionmentioning
confidence: 99%